Renal Artery Stenosis in Patients with Peripheral Artery Disease: Prevalence, Risk Factors and Long-term Prognosis. (March 2017) - Aboyans, V.; Desormais, I.; Magne, J.; Morange, G.; Mohty, D.; Lacroix, P.
Abstract : Objective/Background: The objective was to determine the prevalence and clinical determinants of renal artery stenosis (RAS) in patients undergoing digital subtraction angiography (DSA) for the assessment of peripheral artery disease (PAD), and to evaluate its prognostic significance. Methods: All DSAs performed from January 2000 to January 2006 were retrospectively reviewed for assessment of PAD in patients naive for any prior revascularisation of lower-limb arteries. All DSA studies were read by two senior physicians blinded to outcome, and consensus was reached in cases of disagreement. RAS was defined as the presence of ≥50% stenosis in either renal artery. Patients' electronic medical files were systematically reviewed and follow-up was completed by contact with family physicians until January 2014. The primary outcome was composite, including death, peripheral revascularisation, or any limb amputation. Secondary outcomes were all-cause mortality, and another composite, including death and non-fatal myocardial infarction or stroke or coronary or carotid revascularisation. Results: In total, 400 consecutive patients having a first DSA of lower extremities, two thirds of whom were for critical limb ischaemia, were studied. Thirteen patients were excluded owing to poor renal artery imaging. RAS was detected in 57 patients (14%). Only two factors were independently and significantly associated with RAS in multivariate analysis: diffuse PAD (involving both proximal and distal segments [odds ratio OR 3.50, 95% confidence interval CI 1.16–10.54; p = .026]) and decreased glomerular filtration rate (OR 0.55 per 30 mL/minute/1.73 m 2, 95% CI 0.41–0.75; p < .001). During follow-up (mean ± SD 62 ± 47 months), 25% experienced limb amputation and 54% died. In multivariate analysis, no significant association was found between RAS and primary outcome (hazard ratio 0.80; 95% CI 0.57–1.10). No significant association was found with secondary outcomes. Conclusion: Incidental RAS is frequent (14%) among patients with PAD undergoing lower extremity imaging. No difference in outcome in patients with RAS versus those without RAS was seen. Larger studies are necessary to draw definite conclusions.